AB1065 VISIT COMPLIANCE IN PATIENTS WITH FAMILIAL MEDITERRANEAN FEVER: RESULTS FROM A GAZI UNIVERSITY FMF COHORT. (2nd June 2020) - Bilici Salman, R.; Avanoğlu Güler, A.; Satiş, H.; Karadeniz, H.; Babaoglu, H.; Atas, N.; Haznedaroglu, S.; Ozturk, M. A.; Goker, B.; Tufan, A.
Abstract : Background: Follow-up in all rheumatologic patients is critical, particularly Familial Mediterranean Fever (FMF). Current recommendations for all experts by the EULAR state that patients with FMF should be evaluated 6-monthly intervals to monitore the character and frequency of the attacks and the acute phase response. Disease-related complications such as amyloidosis can be asymptomatic and need only a careful follow-up. Objectives: to quantify this phenomenon and to find predictive factors of visit compliance in patients with FMF. Methods: The study included 474 adult patients with a diagnosis of FMF who followed at the outpatient rheumatology clinic of tertiary university hospital, from January 2018 to December 2018. . Demographic, socioeconomic data, familiy history, comorbid disease, medication history, characteristics, the International Severity Score for FMF (ISSF), autoinflammatory disease damage index (ADDI) were recorded. Visit compliance was defined as the presence of two visits in the outpatient rheumatology clinic for FMF last one year for the purposes set out in EULAR suggestion.Those who had fewer than two visits in the last one year were considered noncompliant. Results: 230 (48.5%) were compliant while 244 (51.5 %) patients were noncompliant with their rheumatology visit. Both compliant and noncompliant patients had similar median age and disease duration. Female sex and being married was increased the visit compliance.The results of the logistic regression model exploring factors associated with compliance indicated that presence of family history in parents, absence of family history in sibling, treatment with biologic agents, other drug using, presence of more than 2 attacks except fever and adequate medical care were important predictors of visit compliance. Conclusion: In conclusion, if FMF patients visit compliance increase, their functionality, medication adherence and quality of life will increase and flares and complication of disease can decrease. Thus, we highlight some recommendations for FMF specialist, patients and health care providers to improve outcomes. Disclosure of Interests: None declared